2008
DOI: 10.1089/end.2008.9711
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Radical Prostatectomy: Perioperative Outcomes of 1500 Cases

Abstract: Our initial series represents one of the largest published series for perioperative outcomes of robotic assisted prostatectomy. Our data demonstrates the feasibility, safety and efficacy of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(134 citation statements)
references
References 17 publications
10
114
2
8
Order By: Relevance
“…The pathologic stage and PSM rates for open, RLP, and RARP series are summarized on Table 4, 16-22,24-28,30,31,33,55-57 Table 5, 33,37,38,[40][41][42][44][45][46][47] and Table 6, 30,31,35,[48][49][50][51][52][53][54]58 respectively. The pathologic stage in the RARP series was of 78.2% pT 2 tumors and 20.5% pT 3 tumors.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…The pathologic stage and PSM rates for open, RLP, and RARP series are summarized on Table 4, 16-22,24-28,30,31,33,55-57 Table 5, 33,37,38,[40][41][42][44][45][46][47] and Table 6, 30,31,35,[48][49][50][51][52][53][54]58 respectively. The pathologic stage in the RARP series was of 78.2% pT 2 tumors and 20.5% pT 3 tumors.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…In radical prostatectomy, the technique of robotic assistance, combining the increased abdominal pressure with a more intuitive handling of surgical instruments, shows a trend towards lower blood loss during surgery [33]. The average blood loss in patients without antiplatelet therapy using robotic assistance is 100-200 ml [34] compared to 800 ml for conventional radical prostatectomy [35]. Whether this holds true for patients under antiplatelet therapy remains to be studied.…”
Section: Hemorrhagic Risks In Urologic Surgerymentioning
confidence: 99%
“…Two patients developed postoperative lymphocele; no description, however, was given of PLND selection criteria, boundaries, number of patients who underwent PLND, or nodal yield. 52 Link et al 53 reported on 1847 consecutive patients who underwent RALP; 1027 (55.6%) of whom also underwent concurrent PLND, with 15 (1.5%) demonstrating LNI; patient selection criteria, anatomic extent of dissection, and nodal yield were not reported.…”
Section: Large Seriesmentioning
confidence: 99%